Doing good or doing well? Image motivation and monetary incentives in behaving prosocially - Dan Ariely; Anat Bracha; Stephan Meier (Institute for the Study of Labor (IZA), 2007)
This paper experimentally examines image motivation the desire to be liked and well-regarded by others as a driver in prosocial behavior (doing good), and asks whether extrinsic monetary incentives (doing well) have a detrimental effect on prosocial behavior due to crowding out of image motivation. By definition, image depends on one's behavior being visible to other people. Using this unique property we show that image is indeed an important part of the motivation to behave prosocially. Moreover, we show that extrinsic incentives interact with image motivation and are therefore less effective in public than in private. Together, these results imply that image motivation is crowded out by monetary incentives; which in turn means that monetary incentives are more likely to be counterproductive for public prosocial activities than for private ones.
Keywords: 330; Soziales Verhalten; Wohltätigkeit; Motivation; Ökonomischer Anreiz; Test; Theorie